Occupational Safety and Health Unit for UMP workers - UMP, PNC (Penerbit UMP, 2009)
This unit comes under the purview of the Department of Research and Innovation aims to manage aspects relating to the safety and health of university personnel in line with regulations set by the Occupational Safety and Health Act 1994. The UMP management board is concerned with all aspects of safety within the university in efforts to ensure the well-being of its staff and students that they work under safe conditions as stupilated under the Act.